Cetyltrimethylammonium bromide-silica membrane for seawater desalination through pervaporation - Singh, Puyam S.; Chaudhri, Sanjay G.; Kansara, Ankit M.; Schwieger, Wilhelm; Selvam, Thangaraj; Reuß, Stephanie; Aswal, Vinod K. (Bulletin of Materials Science, 2015)
A simple preparation of mesostructured cetyltrimethylammonium bromide (CTAB)-silica membrane is reported. It effectively desalinates seawater to pure water through pervaporation separation process. The membrane thickness was of nanometer-length-scale obtained by deposition of CTAB-silica colloids on porous polysulfone support. Scanning electron microscopy (SEM), atomic force microscopy (AFM) and transmission electron microscopy (TEM) studies were performed to characterize the membrane while the structure of the colloids in coating solution was probed by small-angle neutron scattering (SANS). The prepared membranes exhibited excellent salt rejection efficiency of 99.9% in desalination of synthetic seawater of 40,000 ppm NaCl by pervaporation at 25(a similar to)C. The pure water flux was in the range of 1-2.6 kg m(-2) h depending upon the membrane configuration and thickness. The flux could be greatly enhanced by operating the process at higher temperatures of 40-80(a similar to)C but it was at the cost of decreased salt-rejection efficiency. The initial rejection efficiency and flux of the membrane was found to be restored upon cooling the membrane back to room temperature.
Keywords: Seawater desalination; cetyltrimethylammonium bromide-silica membrane; pervaporation

Nanocrystalline Zeolite Tetraethylammonium-Beta Membrane for Preferential Sorption and Transport of CO2 over N2 - Singh, Puyam S.; Selvam, Thangaraj; Reuß, Stephanie; Avhale, Abhijeet; Lopez Orozco, Sofia; Schwieger, Wilhelm (Chemical Engineering & Technology, 2013)
CO2/N2 gas separation was performed over a nanocrystalline zeolite tetraethylammonium (TEA)-beta membrane prepared on a stainless-steel porous disc by repeated hydrothermal crystallization. Two to three consecutive hydrothermal syntheses were required to form a membrane comprised of a continuous and compact layer of zeolite beta nanocrystals on the support. The membrane TEA-BEA3 obtained by three consecutive syntheses, in which the membrane from two consecutive syntheses was used as support, exhibited the highest structural order. When the separation experiment was performed over this membrane without applying any external applied pressure, 100% selectivity of CO2 over N2 was observed. The separation was driven by differences in chemical potentials of the molecules generated only by the adsorption-desorption behavior of the gases into the membrane. The novel zeolite TEA-beta membrane provided promising results for the separation of small gas molecules due to the combined influence of diffusion and sorption selectivity.
Keywords: CO2/N-2 separation; Hydrothermal crystallization; Nanocrystalline zeolite; Tetraethylammonium-beta membrane

Preparation of ZSM-5 zeolite membranes by combined hydrothermal synthesis and electrophoretic deposition - Negishi, Hideyuki; Reuß, Stephanie; Schwieger, Wilhelm; Boccaccini, Aldo R. (Key Engineering Materials, 2015)
The preparation of a ZSM-5 zeolite membrane on porous stainless steel disk by hydrothermal synthesis with electrophoretic deposition (EPD) as a seeding method was investigated. Micron size ZSM-5 crystal powder was seeded by EPD on the support disk by using ZSM-5 powder dispersed in ethanol. The seeded amounts were easily controlled by the deposition time during EPD. The membrane after secondary growth had a low amount of zeolite in comparison with the in situ seeding method and the permeance of single gas such as He, N2 and CO was also low in comparison with that of the in situ seeding method.
Keywords: Electrophoretic deposition (EPD); Permeance; Secondary growth; Seeding; Zeolite membrane

Sequential Template Decomposition to Adjust the Performance of Imperfect Zeolite BEA Membranes - Reuß, Stephanie; Reif, Benjamin; Sanwald, Dirk; Schwieger, Wilhelm; Kaspereit, Malte; Singh, Puyam S.; Al-Thabaiti, Shaeel A.; Basahel, Sulaiman N.; Mokhtar, Mohamed; Obaid, Abdullah Y.; Alyoubi, Abdulrahman O. (Chemie Ingenieur Technik, 2019)
Zeolite membranes offer superior thermal, chemical, and mechanical stability compared to polymeric membranes. However, it is still a challenge to prepare completely defect-free membranes without any intercrystalline voids, which is necessary for gas separation processes. In this study zeolite beta (*BEA) membranes on stainless-steel supports were prepared by applying the multiple in situ crystallization technique. The membranes were used as a model system to systematically study the decomposition of the organic structure directing agent tetraethylammoniumhydroxide (TEA-OH). It was evaluated if the organic decomposition products of TEA-OH can be used for enhancing the membranes selectivity. Post-treatment experiments have been carried out to adjust surface properties and pore size dimensions in the zeolitic membrane layer. The results show that membranes calcined at lower temperatures exhibit a higher gas selectivity.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Gas separation; Template decomposition; Zeolite BEA membrane

Simulation of One-Stage Dimethyl Ether Synthesis over a Core-Shell Catalyst - Ding, Wenjin; Klumpp, Michael; Lee, Seungcheol; Reuß, Stephanie; Al-Thabaiti, Shaeel A.; Pfeifer, Peter; Schwieger, Wilhelm; Dittmeyer, Roland (Chemie Ingenieur Technik, 2015)
A spherical microsized core-shell catalyst (CuO/ZnO/Al2O3@H-ZSM-5) was synthesized for direct dimethyl ether synthesis from syngas in a micro packed bed reactor. To assist in the preparation and optimization of the core-shell catalyst, a 1D heterogeneous model was developed to simulate diffusion and reactions within the catalyst particles. Using the data obtained from the tubular reactor, kinetic parameters for the catalyst were determined first. Furthermore, simulation showed that thickness and activity of shell have significant effect on the catalytic performance of the core-shell catalyst.
Keywords: Core-shell catalyst; Heterogeneous model; Surface diffusion model; Zeolite H-ZSM-5

Zeolite-Coated Porous Arrays: A Novel Strategy for Enzyme Encapsulation - Marthala, Venkata; Friedrich, Mona; Zhou, Zhou; Distaso, Monica; Reuß, Stephanie; Al-Thabaiti, Shaeel A.; Peukert, Wolfgang; Schwieger, Wilhelm; Hartmann, Martin (Advanced Functional Materials, 2015)
Zeolite Beta-coated stainless steel supports with gradient porosity are employed as filter-panels for lipase encapsulation. Enzyme encapsulation on the stainless steel porous discs is achieved via vacuum infiltration. Subsequently, two lipase-encapsulated zeolite Beta-coated stainless steel discs are attached using an adhesive. The zeolite Beta layer on the stainless steel discs largely prevents lipase leaching in comparison to the stainless steel discs without a zeolite layer. The activity of the lipase-encapsulated, attached zeolite Beta-coated stainless steel porous discs depends on the thickness of the zeolite Beta layer. It is shown that the biocatalytic performance of the lipase-encapsulated, attached zeolite Beta-coated stainless steel supports with a zeolite Beta layer thickness of ≈0.7–1 μm is better than the lipase-encapsulated, attached zeolite Beta-coated stainless steel supports with a zeolite Beta layer thickness of ≈2–3 μm in the lipase-catalyzed transesterification of vinyl propionate with 1-butanol using n-hexane as solvent.